2015
DOI: 10.2183/pjab.91.25
|View full text |Cite
|
Sign up to set email alerts
|

Criticality features in ULF magnetic fields prior to the 2011 Tohoku earthquake

Abstract: The criticality of ULF (Ultra-low-frequency) magnetic variations is investigated for the 2011 March 11 Tohoku earthquake (EQ) by natural time analysis. For this attempt, some ULF parameters were considered: (1) Fh (horizontal magnetic field), (2) Fz (vertical magnetic field), and (3) Dh (inverse of horizontal magnetic field). The first two parameters refer to the ULF radiation, while the last parameter refers to another ULF effect of ionospheric signature. Nighttime (L.T. = 3 am ± 2 hours) data at Kakioka (KAK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 14 publications
(23 reference statements)
5
47
0
Order By: Relevance
“…see Refs. [63][64][65][66] for such phenomena observed before t he M = 9 Tohoku mega-earthquake on 11 March 2011) show that the main characteristics (e.g., amplitude, frequency range, lead time) of these precursory changes are similar to those discussed above for SES (which, as mentioned, for strong impending earthquakes are accompanied by detectable magnetic field variations). This observation has prompted the application [67] of the aforementioned criteria (Eq.…”
Section: Results For the Electric And Magnetic Signals That Precede Rsupporting
confidence: 63%
“…see Refs. [63][64][65][66] for such phenomena observed before t he M = 9 Tohoku mega-earthquake on 11 March 2011) show that the main characteristics (e.g., amplitude, frequency range, lead time) of these precursory changes are similar to those discussed above for SES (which, as mentioned, for strong impending earthquakes are accompanied by detectable magnetic field variations). This observation has prompted the application [67] of the aforementioned criteria (Eq.…”
Section: Results For the Electric And Magnetic Signals That Precede Rsupporting
confidence: 63%
“…However, we have to mention that the mechanisms for both phenomena are not well understood, and require further investigation [30]. Our non-conventional analysis based on critical analysis has yielded the presence of lithospheric ULF radiation for the 2011 Tohoku EQ [26], even though no clear signature in lithospheric ULF radiation was found by the conventional statistical analysis for this EQ. The lithospheric ULF radiation is again not so evident for this Kumamoto EQ event, but our future paper [29] will indicate a possibility of finding out criticality even for this Kumamoto EQ event.…”
Section: Discussionmentioning
confidence: 94%
“…But, we cannot come to any definite conclusion on the presence of precursory ULF radiation with this conventional statistical analysis. So that, we have to proceed to the non-conventional analysis such as the application of natural time to these ULF data (e.g., [26] [27] [28]), and those national time results will be published elsewhere [29].…”
Section: A Schekotov Et Al Open Journal Of Earthquake Researchmentioning
confidence: 99%
“…In addition, as the radial component of the Earth's magnetic field can be used as a measure of the variations in the CMB in periods of time of several months or years, we looked for significant variations in the geomagnetic spectra associated with other major geological events in the Chilean margin, as the latest research shows a statistically significant relation between geomagnetism and earthquakes (Hayakawa and Molchanov, 2002;Pulinets and Boyarchuk, 2004;Varotsos, 2005;Hayakawa et al, 2007Hayakawa et al, , 2015; Molchanov and Hayakawa, 2008;Liu, 2009;De Santis et al, 2015Contoyiannis et al, 2016;Potirakis et al, 2016a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, there is a great amount of recent and rigorous research that has shown a statistical relation between magnetism and earthquakes, and thus, this effect could not be negligible in other magnetic properties, such as the Rc or the study of particle flux at Earth's ground level (Hayakawa et al, 2015;Contoyiannis et al, 2016;Potirakis et al, 2016a, b;De Santis et al, 2017;Oikonomou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%